2021
DOI: 10.1039/d1dt00519g
|View full text |Cite
|
Sign up to set email alerts
|

Strong circularly polarized luminescence of mixed lanthanide coordination polymers with control of 4f electronic structures

Abstract: This paper reports chiral mixed Eu(iii)–Ln(iii) coordination polymers (Ln = Gd and Sm) for the enhancement of the emission quantum yield (Φtot ≥ 50%), achieved via control of 4f electronic structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Based on intermolecular interactions, Fujiki et al [136] achieved chirality induction and CPL from racemic polyfluorene using cellulose derivatives as template. Some studies have further demonstrated that CPL-active hybrids can be fabricated when luminescent metal ions are coordinated with chiral polymers [137][138][139][140].…”
Section: Constructing Cpl-active Polymers Via Physically Blendingmentioning
confidence: 99%
“…Based on intermolecular interactions, Fujiki et al [136] achieved chirality induction and CPL from racemic polyfluorene using cellulose derivatives as template. Some studies have further demonstrated that CPL-active hybrids can be fabricated when luminescent metal ions are coordinated with chiral polymers [137][138][139][140].…”
Section: Constructing Cpl-active Polymers Via Physically Blendingmentioning
confidence: 99%
“…Recently, the photophysical and theoretical analyses of the LMCT excited states, which affect the 4f–4f transition probability in Eu­(III) complexes, have been focused on. We considered that the chiroptical properties of chiral Eu­(III) compounds are also affected by the LMCT transition. Thus, the transition electric dipole moments of the LMCT states were estimated by TD-DFT calculations to understand the mechanism of the g CPL change under structural transformation.…”
Section: Resultsmentioning
confidence: 99%
“…The constructions of CPL-active coordination helicates, MOPs, and MOFs have attracted much attention in the past decade and some of them are of practical use in enantioselective recognition and separation, asymmetric catalysis, nonlinear optics, etc. [77][78][79][80][81][82][83][84]…”
Section: Cpl-active Aggregates Of Coordination Helicates Polymers And...mentioning
confidence: 99%